A Study Seeking Historical Evidence for Bases of Classified Balance Sheets - Pekdemir, Recep; Flesher, Dale L.; Aslan, Ümmühan; Ercan, Melis (Journal of Accounting and Finance, 2024)
This paper explores the historical evolution of balance sheet layout and the reasons behind the positioning of assets on the left or right side. It delves into two main questions: why the discrepancy in asset placement on balance sheets across countries, and why the shift from right to left in the UK during the 19th century. Using historical evidence spanning from the 15th century to the mid-20th century, the study investigates the development and changes in listing assets, liabilities, and stockholders' equity. It aims to uncover the factors influencing the classification and presentation of items on balance sheets, driven by the needs of information users over time. By examining secondary sources in English literature, the paper provides insights into the evolution of balance sheet layouts globally. Researchers may find this exploration of historical balance sheet variations intriguing, shedding light on how layout decisions have been shaped by user needs and expectations.